A preliminary behavior analytic approach to "Sundowning" among older adults with major neurocognitive disorder. Issue 2 (2nd July 2016) - Stadlober, Lily; Sharp, Rebecca A.; Mudford, Oliver C.
ABSTRACT: Research has estimated that "sundowning", an increase in confusion, agitation or challenging behavior later in the day, occurs in 20–40% of people with Alzheimer's disease (AD). We conducted 8-h continuous measurement of the sundowning behavior of two women with AD who were identified as "sundowners" by staff in a care home. The distribution of behavior corresponded to the description of sundowning for one participant, but not the other. Functional analysis results suggested a possible social positive function for one participant but were unclear for the other. We suggest that sundowning is better defined as a description of the distribution of behavior across a day rather than topographically, because topography and function differ across individuals. We recommend that environmental variables such as staff attention should be measured to determine their effect on behavior and to develop interventions. This study demonstrates an example of a behavior analytic approach to clinical practice in dementia settings, including potential limitations.